A Journey to be Eco-Tourism Destination: Bali Prepared to Shift into Electric-based Vehicle - I.B. Komang Surya Werdiyasa (Bali Tourism Journal, 2020)
Indonesia is planning to shift its astronomical number of fossil-fueled vehicles to electric-based. The implementation started from Presidential Regulation Number 55 of 2019 issuance concerning the Battery Electric Vehicle Program Acceleration for Road Transportation to stop air pollution ultimately. Whereas in Bali, Governor Wayan Koster issued governor regulations number 45 & 48 of 2019 to serve as the legal basis for Electric Vehicle (EV) infrastructure development. To stimulate the Bali island's eco-friendly atmosphere, PT Jasamarga Bali Tol, who manages Bali Mandara Toll Road (Nusa Dua - Ngurah Rai - Benoa), launched a Public Electric Vehicle Charging Station. The Ministry of State-Owned Enterprises (BUMN) also requested PT Pertamina (Persero) to produce electric car batteries instead of only fossil fuels. For the electric vehicle battery concept, State-owned Minister Erick Thohir has negotiated with international battery manufacturers. Private companies are also involved in promoting eco-friendly vehicles, such as Grab collaborated with Bali Main Distribution Unit (UID), Bali Province Transportation Agency, PT Pegadaian, Astra Honda Motor, and Panasonic. Then, the Japanese car manufacturer, Toyota, plans to develop the Electric Vehicle Smart Mobility project in Bali to support Nusa Dua, Bali's ecotourism ecosystem. Although EV would help reduce air pollution, The Central Government must inspect the electric vehicle power source since most power plants in Indonesia are coal-fired power stations (PLTU). To solely depend on electric vehicle usage would not have a tremendous impact.